Energy Management of Grid Connected PV-Wind-Battery Hybrid Power Supply System Using Model Predictive Control - Hnin Nwe; Wunna Swe (The Indonesian Journal of Computer Science, 2026)
The increasing integration of renewable energy sources into modern power systems presents significant challenges in energy management due to their intermittent and uncertain nature. This paper proposes an energy management strategy for a grid connected photovoltaic (PV), wind and battery hybrid system based on Model Predictive Control (MPC). The main objectives are to enhance system efficiency, minimize grid power exchange and extend battery lifetime while ensuring reliable load supply. The proposed MPC-based EMS employs short-term forecasts of renewable generation and load demand to optimize power dispatch under system constraints. Its performance is evaluated and compared with a conventional rule-based EMS using MATLAB/Simulink. The results indicate that the MPC-based approach achieves smoother battery operation, improved state-of-charge regulation, enhanced renewable energy utilization and reduced grid dependency. Therefore, the proposed strategy provides on effective solution for advanced hybrid renewable energy systems.